Antibacterial, injectable, and adhesive hydrogel promotes skin healing - Fang, Zilong; Lin, Tao; Fan, Shuai; Qiu, Xing; Zhong, Ziqing; Yang, Ganghua; Yang, Jianqiu; Zhang, Guoqing; Feng, Yang; Ai, Fanrong; Shi, Qingming; Wan, Wenbing (Frontiers in Bioengineering and Biotechnology, 2023)
With the development of material science, hydrogels with antibacterial and wound healing properties are becoming common. However, injectable hydrogels with simple synthetic methods, low cost, inherent antibacterial properties, and inherent promoting fibroblast growth are rare. In this paper, a novel injectable hydrogel wound dressing based on carboxymethyl chitosan (CMCS) and polyethylenimine (PEI) was discovered and constructed. Since CMCS is rich in -OH and -COOH and PEI is rich in -NH2, the two can interact through strong hydrogen bonds, and it is theoretically feasible to form a gel. By changing their ratio, a series of hydrogels can be obtained by stirring and mixing with 5 wt% CMCS aqueous solution and 5 wt% PEI aqueous solution at volume ratios of 7:3, 5:5, and 3:7. Characterized by morphology, swelling rate, adhesion, rheological properties, antibacterial properties, in vitro biocompatibility, and in vivo animal experiments, the hydrogel has good injectability, biocompatibility, antibacterial (Staphylococcus aureus: 56.7 × 107 CFU/mL in the blank group and 2.5 × 107 CFU/mL in the 5/5 CPH group; Escherichia coli: 66.0 × 107 CFU/mL in the blank group and 8.5 × 107 CFU/mL in the 5/5 CPH group), and certain adhesion (0.71 kPa in the 5/5 CPH group) properties which can promote wound healing (wound healing reached 98.02% within 14 days in the 5/5 CPH group) and repair of cells with broad application prospects.